Gas-phase deposition of cavitation-resistant coatings based on boron carbide - A. Yu. Zhuravlov; A. V. Shijan; B. M. Shirokov (Хімія, фізика та технологія поверхні)
Reliability and profitability of NPP operation of any type to a large extent depend on the reliable operation of the system of its pipelines. From literary sources is shown that the most dangerous zone, in terms of erosion wear, is a pipeline fluctuation. Solving the problem of erosion wear of the zone of the twists of the pipelines is possible by gas phase depositing protective coatings based on boron carbide, which slow down the cavitation processes of wear. This paper presents the results of studies on the production of a cavitation-resistant coating based on boron carbide by hydrogen reduction of boron trichloride BCl3 and toluene C7H8. Boron carbide was carried out on a plant with a horizontal flow-type reaction chamber. The principle of its operation consists in passing through the reaction chamber of the vapor-gas flow of reagents entering the chemical reaction on the surface of the heated substrate located inside the reaction chamber. Solid phase reaction products form an increasing condensate layer on the substrate surface and gaseous products are removed from the reaction chamber and neutralized. Trichloride boron BCl3 and toluene C7H8 were selected as reagents. Carrying gas and activator was hydrogen H2. Deposition was carried out on the austenitic steel substrate. It was shown that morphology of the surface is characterized by grapple-scraped globules. X-ray spectral studies have shown that the distribution of elements is uniform, this indicates that when austenitic steel is heated, no significant changes in properties occur. Diffractometric studies have shown that coating contains grain of Fe2B iron boride and Fe7C3 iron carbide. measurement microhardness have shown that from the center of the substrate to the side of the coating is increased in double. Destruction of samples under the influence of cavitation was studied on the installation of ultrasound cavitation. The cavitation zone was formed between the end of the emitter, which is connected with an ultrasonic generator of UZG-3 0.4 type, and the surface of the test specimen installed in water having the temperature of 293 K. For comparison, the kinetic curve of the destruction of the standard A18H10T austenitic steel and a boron carbide-based sample is given. Under the same test conditions, the nature of the kinetic curves is different. A sample with a carbide-borne coating is 2.5 times less cavitation wear than austenitic steel.